The path of least resistance: Constructions of space in the discourse of Israeli military refuseniks. (December 2015) - Livio, Oren
Abstract: In this article I examine the ways in which Israeli soldiers who refuse to serve in the Occupied Territories use spatial representations and metaphors in discourse explaining their decision to refuse. Using Lefebvre's (1995) framework regarding spaces of representation as sites of political struggle, I analyze how selective refuseniks construct the Territories as a space of pollution, irrationality, disorder and death, expressing fear that these qualities might contaminate Israeli space, and thus implicitly promoting a separatist logic of exclusion. Refuseniks employ metaphors of movement to portray the transition from 'here' to 'there' as a shift into an alternate universe, and attempt to appropriate hegemonic discursive conceptualizations associated with three culturally loaded spaces: the prison, the Jewish settlements, and Nazi Germany. The ambivalent dialectics of dominant and resistant ideologies in refuseniks' discourse and their cultural implications are discussed. Highlights: I examine spatial constructions in the discourse of Israeli selective refuseniks. Refuseniks create a binary opposition between Israel and the Occupied Territories. The Territories are constructed as polluted, thus rendering Israel pure. The main concern is that the space of the Territories will seep into Israel. Despite resistant content, spatial constructions and metaphors are often hegemonic.